Auditor Tenure and Stock Price Volatility: The Moderating Role of Auditor Industry Specialization - Mehran Jorjani; Mehdi Safari Gerayeli (Australasian Accounting, Business and Finance Journal, 2018)
Purpose The present study aims to investigate the relationship between auditor tenure and stock return volatility and to study the moderating effect of auditor’s industry specialization on this relationship in the firms listed on the Tehran Stock Exchange (TSE). Design/methodology/approach A sample of 95 companies listed on the Tehran Stock Exchange during the period 2011 to 2015 was selected and two hypotheses were formulated and analyzed using multivariate regression and econometric models. Findings The results of the study indicate that with the increase of auditor tenure, the volatility of stock returns is reduced. However, the results showed that the use of auditors specializing in the client's industry does not affect the relationship between the length of auditor tenure and the volatility of stock returns. Originality/value The findings of current study not only extend the extant theoretical literature concerning the stock price volatility in developing countries including emerging capital market of Iran, but also help investors, capital market and audit profession regulators to make informed decisions.
Keywords: auditor tenure; auditor industry specialization; stock return volatility.